Smart glazing systems: An industrial outlook - Samantha Wijewardane; Matthaios Santamouris (Solar Compass)
Windows play a pivotal role in the building envelope, significantly influencing energy performance, aesthetic appeal, and overall occupant comfort. The design of a glazing system that optimally integrates all relevant factors poses considerable challenges. Smart glazing technologies, capable of dynamically adjusting their optical properties in response to varying outdoor conditions, have shown a promising potential to enhance energy efficiency without compromising the architectural integrity of structures. This paper provides a thorough review of commercially available smart window technologies, examining aspects such as their underlying technologies, manufacturing processes, marketing strategies, energy performance metrics, aesthetic qualities, and the barriers they face in capturing a larger market segment. The smart glazing systems considered include Electrochromic (EC), thermochromic (TC), thermotropic (TT), photochromic (PC), SPD (Suspended Particle Devices) Smart windows, PDLC (Polymer Dispersed Liquid Crystal) and PNLC (Polymer Network Liquid Crystals) smart windows. In the discussion section, we summarize the principal findings and explore strategic pathways to address the current challenges hindering broader adoption of these advanced glazing solutions.